Solitary bone cyst coexistent with tooth agenesis: Unique case report and brief review - Sanjay Reddy Podduturi; Ashalata Gannepalli; Bhargavi Krishna Ayinampudi; Poornima Ksheerasagara (Wolters Kluwer Medknow Publications, 2014)
Solitary bone cysts (SBCs) exist generally as asymptomatic solitary lesions and have no epithelial lining. They are uncommon in the jaws and are often polymorphic, show scalloped borders when located between the roots. They have higher predilection for the posterior mandible, mostly occurring near the mental foramen. Various pathomechanisms were proposed, but the triggering factor still remains to be ascertained. Currently, osteolytic pathogenesis is speculated, which may be due to vascular alteration leading to aseptic osseous necrosis. Fibro-osseous lesions are occasionally associated with SBCs, but concomitant presence with tooth agenesis has not been reported. We present a unique case of SBC with familial tooth agenesis in a 16-year-old female patient with a brief review.